Adoption of the balanced scorecard in local government organizations: an exploratory study / Sujatha Perera, Herbert Schoch, and Saba Sabaratnam - Perera, Sujatha (Accounting Research Institute, Faculty of Accountancy & UiTM Press, 2007)
Despite the recent attention on the balanced scorecard as a performance measurement system, the extent of adoption of the Balanced Scorecard (BSC) in different organizational settings is not well known. This study adds to the existing literature on the BSC by examining its use in local governments. The study examines the extent of adoption of the BSC in local governments and the factors that appear to influence its adoption.